PERANAN KOMUNIKASI DALAM KELUARGA TERHADAP PEMBENTUKAN JATI DIRI REMAJA - Effiati Juliana Hasibuan (Universitas Medan Area, 2012)
One of the biggest challenges of adolescence is constructing their self-identity. Teens between the ages of 13 and 21 are not only maturing physically, but they are also growing into their new role as adults. In order to do this, they need to answer for themselves the question